USULAN PERBAIKAN PROSES PRODUKSI LAMPU LED BERBASIS LEAN MANUFACTURING UNTUK MENINGKATKAN OUTPUT DI PT XYZ - Nazela Afaf; Hardiana Widyastuti; Suhendi Irawan (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2026)
PT XYZ faces challenges in meeting the daily production target for LED lamps, with an average achievement of only 89% of the target of 400 units per day. This research aims to identify waste and design improvement proposals using a lean manufacturing approach within the DMAIC (Define, Measure, Analyze, Improve, Control) framework. Based on observations and Value Stream Mapping (VSM), a significant bottleneck was identified at station 3 with a cycle time of 255 seconds, triggered by rework activities and ergonomic constraints. The proposed improvements include standardizing work methods and optimizing tools to eliminate Non-Value Added (NVA) activities. Through these improvements, it is expected that assembly line efficiency will increase, allowing the total production target of 10,000 units to be completed on time.